Contribution of digital radiology in analysis of cardiovascular structures, pulmonary vessels, and signs of congestive heart failure in dogs - Jojima, Flavio Shigueru, 1980- (2018)
Orientadora: Profª. Drª. Tilde Rodrigues Froes